Chemodiversity of the Glucosinolate-Myrosinase System at the Single Cell Type Resolution - Chhajed, Shweta; Misra, Biswapriya B.; Tello, Nathalia; Chen, Sixue (Frontiers in Plant Science, 2019)
Glucosinolates (GLSs) are a well-defined group of specialized metabolites, and like any other plant specialized metabolites their presence does not directly affect the plant survival in terms of growth and development. However, specialized metabolites are essential to combat environmental stresses, such as pathogens and herbivores. GLSs naturally occur in many pungent plants in the order of Brassicales. To date, more than 200 different GLS structures have been characterized and their distribution differs from species to species. GLSs co-exist with classical and atypical myrosinases, which can hydrolyze GLS into an unstable aglycone thiohydroximate-O-sulfonate, which rearranges to produce different degradation products. GLSs, myrosinases, myrosinase interacting proteins, and GLS degradation products constitute the GLS-myrosinase (GM) system (‘mustard oil bomb’). This review discusses the cellular and subcellular organization of the GM system, its chemodiversity, and functions in different cell-types. Although there are many studies on the functions of GLSs and/or myrosinases at the tissue and whole plant levels, very few studies have focused on different single cell-types. Single cell-type studies will help to reveal specific functions that are missed at the tissue and organismal level. This review aims to highlight: (a) recent progress in cellular and subcellular compartmentation of GLSs, myrosinases, and myrosinase interacting proteins; (b) molecular and biochemical diversity of GLSs and myrosinases; and (c) myrosinase interaction with its interacting proteins, and how it regulates the degradation of GLSs and thus the biological functions (e.g., plant defense against pathogens). Future prospects may include targeted approaches for engineering/breeding of plants and crops in the cell-type specific manner towards enhanced plant defense and nutrition.